PENGARUH KINERJA KEUANGAN PEMERINTAH DAERAH TERHADAP KESEJAHTERAAN MASYARAKAT PADA KABUPATEN/KOTA DI PROVINSI JAWA TIMUR - Evlyn, Mahardika; Rahayu, Yuliastuti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2018)
This research is aimed to examine the influence of local government financial performance which is measured by using the degree of decentralization, the ratio of local financial independence, and the ratio of the effectiveness of local own source revenue (PAD) to the Human Development Index (IPM) which is used as the standard of community welfare in terms of public services in the Districts / Cities in East Java Province. The approach has been carried out by using quantitative approach and multiple linier regressions analysis method. The population is 38 Districts / Cities East Java Province. The data is the secondary data in the form of Budget Realization Report (LRA) from 2014 to 2016. The data has been obtained from Local Finance and Asset Management Board (BPKAD) of East Java Province and the official website of Central Bureau of Statistics (BPS) of East Java Province. The data has been processed by using 21st version SPSS application. The result of this research indicates that the degree of decentralization gives positive influence to the Human Development Index and the ratio of local financial independence gives negative influence to the Human Development Index. Meanwhile the ratio of the effectiveness of local own source revenue does not give any influence to the Human Development Index.Keywords: Decentralization degree, local financial independence ratio, effectiveness ratio of PAD, humandevelopment index (HDI).